(untitled) (Majalah Kedokteran Bandung, 2026)
Conjunctivitis is one of the most common ocular infections encountered in clinical and hospital settings, particularly among children under seven years of age. This study aimed to evaluate the antimicrobial susceptibility of ophthalmic isolates of Staphylococcus aureus to different antibacterial agents and to compare the effectiveness of antibiotics, plant extracts, and green-synthesized silver nanoparticles (Ag-NPs). A cross-sectional study was conducted from June 2024 to June 2025. Clinical samples were collected from Fatima Memorial Hospital, Lahore, India, and cultured on Mannitol Salt Agar to isolate S. aureus. Isolates exhibiting β-hemolysis on blood agar were selected and subjected to antimicrobial susceptibility testing against selected antibiotics, plant extracts, lactic acid bacteria (LAB), and Ag-NPs. Four isolates demonstrated β-hemolysis, confirming pathogenic S. aureus association with ocular infections. Among the antibiotics tested, strain 3 showed the highest susceptibility to levofloxacin, with an inhibition zone of 22±0.06 mm. In contrast, Syzygium aromaticum extract showed significant antibacterial activities, with inhibition zones of 12.88±0.86 mm and 11.6±0.68 mm for strains 1 and 2, respectively, while strain 4 exhibited lower susceptibility. The LAB also demonstrated antibacterial activities, although the inhibitory effect was gradual. Ophthalmic isolates of Staphylococcus aureus exhibit resistance to several commonly used antibiotics. Plant extracts and green-synthesized Ag-NPs demonstrate considerable antibacterial activities, suggesting their potential as alternative therapeutic agents for ocular infections.